Good Corporate Governance and Financial Condition on Firm Value During the Covid-19 Era - Priscilia, Vina; Rudyanto, Astrid (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2024)
The purpose of this research is to get empirical evidence regarding the influence of board of commissioner, board of director, institutional ownership, profitability, tax planning, company size, and capital structure on firm value. The population in this research is consumer cyclical and consumer non-cyclical companies listed in the Indonesia Stock Exchange (IDX) during the years 2020-2022. This research used multiple linear regressions. The result of this research shows that board of director and company size, have a positive influence on firm value. Meanwhile, profitability has a negative influence on firm value. But board of commissioner, institutional ownership, tax planning, and capital structure have no influence on firm value. Based on the results of one research, profitability that investor tends not to believe in companies that have profit during covid-19 because they think that the companies make earnings management to make their company sustain during covid-19 era. Then the companies are advised to be more careful and careful in determining all decisions, include financial condition.